Emission control with route optimization in solid waste collection process: A case study - Apaydin, Omer; Gonullu, M. Talha (SPRINGER INDIA, 2008)
Solid waste collection processes are usually carried out by using trucks with diesel engine. In solid waste collection process, the trucks emit to environment different emissions from its exhausts. For this reason, in solid waste collection process, it is necessary that route optimization should be performed in order to decrease the emissions. This study was performed in Trabzon City with 39 districts, a shortest path model was used in order to optimize solid waste collection/hauling processes to minimize emission. Unless it performs route optimization in solid waste collection/hauling process, emissions increase due to empty miles negativeness. A software was used as an optimization tool. The software provided Geographical Information System (GIS) elements such as numerical pathways, demographic distribution data, container distribution data and solid waste production data. In addition, thematic container layer was having 777 points for the entire city. By using the software, the optimized route was compared with the present route. If the optimized route in solid waste collection system is used, route distance and route time will be decreased by 24.6% and 44.3% as mean of nine routes, respectively. By performing the stationary container collection process and route optimization, it is determined that CO2, NOx, HC, CO, PM emissions will be reduced 831.4, 12.8, 1.2, 0.4, 0.7 g per route, respectively.
Keywords: exhaust emission; route optimization; solid waste collection; GIS; Trabzon; Turkey; Engineering